2016
DOI: 10.1039/c6cp05140e
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Li+ ion transport in a mixed carbonate/LiPF6 electrolyte near graphite electrode surfaces: a molecular dynamics study

Abstract: Electrolyte and electrode materials used in lithium-ion batteries have been studied separately to a great extent, however the structural and dynamical properties of the electrolyte-electrode interface still remain largely unexplored despite its critical role in governing battery performance. Using molecular dynamics simulations, we examine the structural reorganization of solvent molecules (cyclic ethylene carbonate : linear dimethyl carbonate 1 : 1 molar ratio doped with 1 M LiPF) in the vicinity of graphite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 55 publications
10
49
0
Order By: Relevance
“…Furthermore, it was reported that the concentration of the electrolyte mixture (solvent, salt, and additives) and the applied voltage also affect the solvation structure near the surface, and subsequently impact the reduction of the electrolyte. [40][41][42][43][44][45][46][47][48] In particular, the reduction reactions of the SEI depend strongly on the composition of the electrolyte. [46] The ab initio molecular dynamics simulations for a 1 mol/dm 3 LiPF 6 /EC solution showed that the reaction depends on the distance between the anion and the active Li site at the surface because the reduction reaction usually occurs via electron transfer at the surface, although the salt would be expected to reduce first because of its higher reduction potential.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was reported that the concentration of the electrolyte mixture (solvent, salt, and additives) and the applied voltage also affect the solvation structure near the surface, and subsequently impact the reduction of the electrolyte. [40][41][42][43][44][45][46][47][48] In particular, the reduction reactions of the SEI depend strongly on the composition of the electrolyte. [46] The ab initio molecular dynamics simulations for a 1 mol/dm 3 LiPF 6 /EC solution showed that the reaction depends on the distance between the anion and the active Li site at the surface because the reduction reaction usually occurs via electron transfer at the surface, although the salt would be expected to reduce first because of its higher reduction potential.…”
Section: Resultsmentioning
confidence: 99%
“…A later MD simulation by Borodin and Bedrov predicted that the activation energy for Li + de-solvation at the SEI/electrolyte interface is 0.42 (~42 kJ mol −1 ) and 0.46 eV (~47 kJ mol −1 ) for the Li 2 EDC/electrolyte and Li 2 BDC/electrolyte interfaces, respectively. 186 Boyer et al 93 performed MD simulations of this process and showed an accumulation of Li + on graphite surface under different charge densities. These large-scale MD simulations described the electrolyte structural changes under the applied electric field, but have not been able to predict the energetics of electrolyte reduction reactions or the charge transfer reaction, due to the force field limitation.…”
Section: Correlation Of Sei Properties With Battery Performance Starmentioning
confidence: 99%
“…The composition and structure of the SEI layer evolve as a function of the applied potential in a working lithium half-cell. 91 Boyer et al 93 performed MD simulations with a classical force field and demonstrated the different rearrangements of EC and DMC on a graphite edge surface under the applied electric field. Thus, the electrolyte structure rearrangement near the electrode surface will certainly impact the onset of the reduction reactions and the Li + de-solvation process.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
“…This is because net charges opposite to ion are induced on the electrode surface even in the ΔΨ 0 = 0 V case. Although having said that, ions in the equilibrium state are unlikely to be on the electrode surface as shown in previous studies …”
Section: Resultsmentioning
confidence: 84%
“…Although having said that, ions in the equilibrium state are unlikely to be on the electrode surface as shown in previous studies. [33,55] Ion desorption rate by transition state theory. Transition state theory (TST) is another way to estimate a rate constant of many kinds of processes.…”
Section: Edl Relaxation Slowing Down By the Electrode Polarizationmentioning
confidence: 99%